The Effect of Patency Files on Apical Canal Anatomy Using SEM Imaging - Michael S. Cavender; Christopher Waters (International Journal of Dentistry)
Introduction. There are many reasons to maintain apical patency during routine endodontic treatment. Thousands of canals are treated utilizing a patency file every year all around the world. The effect patency has on the apical anatomy of the root has been controversial for generations. Objective. This ex vivo descriptive study was created to show the effect patency files actually have on the apical root canal anatomy using visually detailed SEM images supported by dental radiographs. Materials and Methods. Three extracted maxillary anterior teeth that represent the multitude of canals in vivo were instrumented utilizing patency files. Two of the three maxillary anterior teeth were instrumented with hand files, the other maxillary anterior tooth with a .06 taper rotary file. The teeth were then scanned with an electron microscope to view the effect that the instruments had on the apical canal anatomy. A fourth tooth, a maxillary second molar, was shaped with an .06 taper rotary file and cone fitted. This tooth was radiographed with a gutta percha cone fitted to reveal the position of the narrowest constriction after patency was achieved. Results. The patency files, both hand files and rotary, were shown not to adversely affect the apical canal anatomy. Additionally, the SEM’s revealed a precise demarcation of cementum to dentin which was at the root surface after patency was achieved. Conclusion. The patent use of greater tapered rotary files provides a clear demarcation of the CDJ which allows a precise acquisition of the narrowest constriction of the canal with the use of an electronic apex locator for establishing the ideal working length and precision placement of a gutta percha cone.